The effect of concurrent clopidogrel and omeprazole administration on clopidogrel metabolism and platelet function in healthy cats - Christina Plante; Pamela M. Lee; Jillian M. Haines; O. Lynne Nelson; Stephanie E. Martinez; Michael H. Court (Journal of Veterinary Internal Medicine, 2024)
Abstract Background Some studies in humans show that the concurrent use of clopidogrel and omeprazole decreases plasma clopidogrel active metabolite (CAM) concentrations and clopidogrel antiplatelet effects. Whether this drug interaction occurs in cats is unknown. Hypothesis We hypothesized that administration of clopidogrel with omeprazole would decrease plasma CAM concentrations and decrease clopidogrel antiplatelet effects in healthy cats. Animals Ten domestic cats. Methods In this 2‐sequence, 2‐period, 2‐treatment randomized crossover study, healthy cats were randomly assigned to receive clopidogrel only (18.75 mg PO q24h) or clopidogrel with omeprazole (1 mg/kg PO q12h) for 10 days, followed by a 2‐week washout period, and then the opposite treatment for another 10 days. Blood was collected by jugular venipuncture on days 0, 5, and 10. Plasma CAM concentrations were measured using high‐performance liquid chromatography‐tandem mass spectrometry. Platelet function was evaluated using Plateletworks, Multiplate Analyzer, and Platelet Function Analyzer‐100 (PFA‐100). Results Multiplate Analyzer and PFA‐100 detected no difference in platelet function between days or treatment groups. Plateletworks detected a significant difference (P < .001) in platelet function from day 0 to 5 and day 0 to 10 in both treatment groups but no difference between treatment groups. Plasma CAM concentrations were significantly lower on day 10 (P < .02) in cats receiving both medications versus clopidogrel only. Conclusions and Clinical Importance Concurrent omeprazole and clopidogrel administration was associated with altered pharmacokinetics on day 10, but no difference in pharmacodynamics between the 2 treatment groups. The short‐term use of clopidogrel and omeprazole does not seem to alter platelet function significantly.